A Lacanian understanding of urban development plans under the neoliberal discourse. (August 2021) - Bahmanteymouri, Elham
Urban development and land release policies in the city fringes are criticised because they often fail to achieve their objectives such as providing affordable housing for low to moderate-income groups as well as provision of infrastructure and transportation. From a Marxian point of view, urban development plans fail because of the inherent contradictions of capital, and consequently, maximisation of surplus-value becomes the main objectives of land supply policies. In this paper, I draw on the Lacanian concept of drive and use the homology between Marxian surplus-value and Lacanian surplus-enjoyment to explain how the market rationality of neoliberalism (late-capitalism) deflects the desired objectives of urban development plans (UDPs); that is, the desire to provide affordable housing and urban services and infrastructure instead facilitates speculative activities on land in the suburban areas of a metropolis, such as Perth, Western Australia. In particular, the paper focuses on the neoliberal intuitional and financial dimensions of UDPs. In conclusion, I suggest how planners may deal with the pressure of the lack in the hegemonic discourse of neoliberalism in order to avoid the stuckness of the logic of drive materialised in the operation of planning institutions.